Crystal structure of 1,3,6,8-tetrabromo-9-ethyl-9H-carbazole - Bezuglyi, Mykola (Acta Crystallogr E Crystallogr Commun, 2015)
In the title compound, C(14)H(9)Br(4)N, the tricyclic ring system is almost planar (r.m.s. deviation for the 13 non-H atoms = 0.017 Å) and the methyl C atom deviates from the mean plane of the ring system by 1.072 (17) Å. In the crystal, Br⋯Br contacts [3.636 (3) and 3.660 (3) Å] slightly shorter than the van der Waals contact distance of 3.70 Å are seen.